Keselarasan Manajerial dan Uraian Tugas dalam Keberlanjutan Budaya Mutu Pasca Akreditasi Puskesmas - Maulida Rahmah; Sunarto Sunarto; Utami Utami (Universitas Pahlawan Tuanku Tambusai, 2026)
Accreditation is the principal external quality-assurance instrument for primary health centres (puskesmas), yet the foremost challenge lies in sustaining a quality culture after the survey concludes. Although leadership is recognised as a key structural factor, the relational dynamic between the head of the health centre and the administrative head as a single managerial unit remains rarely examined. Objective: To comparatively analyse how managerial leadership alignment shapes the sustainability of post-accreditation quality culture in two puskesmas with contrasting territorial characteristics and accreditation status. Methods:A qualitative comparative case study was conducted in two puskesmas (urban and rural) within one regency in Jambi Province. Data were gathered through in-depth interviews, non-participant observation, and document review, then analysed thematically using the Donabedian framework. Results: The urban centre exhibited alignment between leadership and administration—personal exemplarity, consistent presence, and a single line of command—that supported the internalisation of quality values. The rural centre experienced misalignment rooted in a structural gap of overlapping job descriptions, producing dual instructions, staff confusion, and weakened sustainability. Conclusion: The alignment of managerial relationships is a crucial structural determinant in the sustainability of a quality culture; the clarity of formal authority distribution needs to be reinforced.